Chiral two bladed ML2 metallamacrocycles: design, structures and solution behavior. Issue 31 (21st July 2017) - Soudry, Hannah; Desmarets, Christophe; Gontard, Geoffrey; Edgington, Tiffany; Cooksy, Andrew L.; Amouri, Hani
Abstract : Chiral two bladed complexes of [Co(L )2 ][BF4 ]2 (1 ) and [Zn(L )2 ][BF4 ]2 (2 ) containing an atropoisomeric semi-rigid bidentate ligandL were synthesized and characterized. Abstract : Chiral two bladed complexes of [Co(L )2 ][BF4 ]2 (1 ) and [Zn(L )2 ][BF4 ]2 (2 ) containing an atropoisomeric semi-rigid bidentate ligandL were synthesized and characterized. They are obtained as homochiral species but in a racemic mixture via a ligand self-sorting mechanism. These enantiomers can be differentiated in solution using optically active anions.